Phenolic compounds in dried herbs and spices commonly used in the kitchen - Natalia Mikołajczak (Kazimierz Wielki University, 2018)
Introduction and aim: Currently, herbs and spices are most often used in a dried form due to low durability of raw materials. They are used to enhance or improve the taste and organoleptic properties of food, to shape the quality of food products, and also as medicines for many generations. They have antioxidant, anti-inflammatory, anti-atherosclerotic and even anti-cancer properties. These health-promoting properties result mainly from the presence of phenolic compounds. The aim of the article was to collect numerical data showing the total content of phenolic compounds and shares of individual phenolic acids and flavonoids in dried herbs and spices commonly used in the kitchen. Brief description of the state of knowledge: The total content of phenolic compounds in dried herbs was 0.01 - 91.40 mg GAE/g d.w. A good source was bay leaf (44.40 - 46.79 mg GAE/g d.w.) and oregano (91.40 mg GAE/g d.w.). However, the content of phenolic compounds in dried spices was in the range of 0.02 - 155.10 mg GAE/g d.w., the dominant amounts contained cinnamon. Small amounts (0.01 - 0.28 mg GAE/g d.w.) of phenolic compounds were found in dried herbs such as lovage, rosemary, lemond bald, sage, and in case of dried species only in turmeric. The shares of phenolic acids in dried herbs were in the range 0.01 (caraway) - 5.17 (thyme) mg/g d.w. for caffeic acid, 0.001 (caraway) - 0.91 (thyme) mg/g d.w. for ferulic acid, 0.01 (caraway) - 0.26 (fennel) mg/g d.w. for chlorogenic acid, and 0.96 (oregano) - 1.64 (lovage) mg/g d.w. for neochlorogenic acid. In the case of dried spices, the shares of individual phenolic acids were 0.01 (ginger) - 0.18 (turmeric) mg/g d.w. for ferulic acid, 0.02 (star anise) - 0.10 (cinnamon) mg/g d.w. for p-coumaric acid, and 0.06 (nutmeg) - 0.21 (star anise) mg/g d.w. for protocatechuic acid. The content of flavonoids in dried herbs and spices was small. A valuable source of luteolin was rosemary (6.16 mg/g d.w.), quercetin was lovage (9.23 mg/g d.w.) and apigenin was rosemary (0.44 mg/g d.w.) and fennel (0.62 mg/g d.w.). Dried spices contained only catechin (curry) and rutin (star anise). Summary: Based on the review of available literature, it can be concluded that dried herbs (bay leaf and oregano) and spices (cinnamon and turmeric) are a good source of phenolic compounds. In addition, dried herbs (oregano, thyme, fennel, lovage) are characterized by the presence of such phenolic acids as caffeic, chlorogenic, and ferulic, while dried spices (cinnamon, star anise) are a source of p-coumaric, protocatechuic and chlorogenic acids. The share of flavonoids in the dried herbs and spices is varied, however dried spices (ginger, cinnamon) contain small amounts of flavonoids.